- #1

- 1

- 0

## Homework Statement

"Find dy/dx at the given point by using implicit differentiation"

x

^{2}y + y

^{2}x = -2 at (2, -1)

and

(x+y)

^{3}= x

^{3}+ y

^{3}

## Homework Equations

## The Attempt at a Solution

1) x

^{2}(dy/dx) + y(2x) + y

^{2}(1) + 2y(dy/dx)(x) = -2

x

^{2}(dy/dx) + 2xy + y

^{2}+ 2xy(dy/dx) = -2

dy/dx(x

^{2}+ 2xy) = 2xy + y

^{2}-2

dy/dx = (2xy + y

^{2}-2)/(x

^{2}+ 2xy)

dy/dx at (2, -1) = (2*2*-1 - 2)/(2

^{2}+ 2*2*-1)

= 0/0 = 0

The first one has me confused, and since the second one is similar I didn't want to attempt it in case I'm completely wrong.